Genital and anorectal mucosal melanoma is associated with cutaneous melanoma in patients and in families. (30th August 2013) - Cazenave, H.; Maubec, E.; Mohamdi, H.; Grange, F.; Bressac‐de Paillerets, B.; Demenais, F.; Avril, M.F.
Abstract : What's already known about this topic? Genital and anorectal mucosal melanomas (GAMMs) are rare. Their genetic and environmental risk factors have been poorly documented. What does this study add? Patients with GAMM or cutaneous melanoma (CM) did not show significant differences for phenotypic risk factors. GAMM and CM may develop in the same patient. There is a noticeable frequency of family history of CM in patients with GAMM, and our findings suggest common genetic determinants to both types of melanomas. Summary: Background: Genital and anorectal mucosal melanomas (GAMMs) are rare compared with cutaneous melanoma (CM). Many epidemiological and genetic studies have been carried out on CM. In contrast, the genetic and environmental risk factors for GAMM have been poorly documented up to now. Objectives: To compare the distribution of pigmentation and naevus phenotypes, sun exposure and family history of melanoma between patients with GAMM and CM. Methods: We compared two series of patients, 81 with GAMM and 293 with CM. Results: Patients with GAMM and CM did not show significant differences for phenotypic risk factors. However, patients with GAMM tended to display red hair (11% vs. 5·5%, P = 0·08) and a poor tanning ability (22% vs. 13·3%, P = 0·06) at a higher frequency than patients with CM. A family history of melanoma was significantly more frequent with GAMM than with CM (18% vs. 7·5%, P = 0·005). Apart from the GAMM index case, affected relatives had CM except in one family. The frequency of multiple primary melanomas (MPMs) was similar in the GAMM and CM series (6% vs. 5·3%, P = 0·43). All patients with GAMM and MPM had only one GAMM primary, while the other primary was cutaneous. No CDKN2A germline mutation was detected in patients with GAMM. Conclusions: This study shows that GAMM and CM may occur in the same patient, and GAMM may develop in a familial setting. The association of both GAMM and CM in patients and families suggests shared genetic factors by these two types of melanoma.